Evaluasi Efektivitas E-Learning Menggunakan Model Kesuksesan Sistem Informasi - dewanty Arzena Wiliyanto, Sabilla; Utomo, Agus Prasetyo; Mariana, Novita (Jurnal Informatika, 2026)
Abstract —  The rapid integration of digital technologies into higher education has positioned e-learning as a fundamental medium for delivering teaching and learning activities. Nevertheless, widespread adoption of e-learning platforms does not necessarily translate into improved learning outcomes. Consequently, assessing the effectiveness of e-learning from an information systems perspective remains an important area of investigation. This study examines the influence of information quality, system quality, service quality, and internet self-efficacy on perceived learning effectiveness by employing the Information Systems Success Model as the underlying theoretical framework. A quantitative research design was adopted, and data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Responses were collected from 206 university students who actively utilize e-learning platforms in their academic activities. The findings reveal that the proposed model accounts for 73.1% of the variance in perceived learning effectiveness. Among the examined factors, system quality demonstrates the strongest contribution, followed by service quality, information quality, and internet self-efficacy. All hypothesized relationships were found to be statistically significant. The results highlight that the effectiveness of e-learning is shaped not only by the technical performance of the platform but also by the quality of supporting services, the relevance of information provided, and users’ confidence in utilizing internet-based technologies. These findings provide empirical evidence for the applicability of the Information Systems Success Model in the context of higher education and offer practical insights for improving digital learning environments.   Key word — e-learning effectiveness; information systems success model; higher education; learning effectiveness.